Tahlil Bunud As'ilah Ikhtibariyah li al-Shaff al-Tsamin fi al-Madrasah al-Mutawassitah al-Islamiyyah al-Hukumiyyah 6 Lima Puluh Kota - Muhamad Ruli Aulia; Rita Febrianta; Yelfi Dewi; Eka Rizal (Al-Lahjah : Jurnal Pendidikan, Bahasa Arab, dan Kajian Linguistik Arab, 2026)
The problem in this research lies in the Arabic language test questions at MTsN 6 Lima Puluh Kota, which have not yet been analyzed. This study aims to determine the quality of Arabic language test items for Grade VIII at MTsN 6 Lima Puluh Kota based on validity, reliability, difficulty level, discriminating power, and distractor effectiveness. The research employs a descriptive quantitative approach. The participants are students from two eighth-grade classes, 8¹ and 8², totaling 63 students. Data were collected through documentation and observation. The data analysis techniques are based on validity, reliability, difficulty level, discriminating power, and distractor effectiveness using Microsoft Excel. The results of the analysis of 30 test items show that 29 items (97%) have good validity, while one item (3%) is invalid. The reliability index is 0.897, indicating high reliability. Regarding the difficulty level, 2 items (7%) are classified as easy, 26 items (86%) as moderate, and 2 items (7%) as difficult. The discriminating power analysis shows that 1 item (3%) needs improvement, 4 items (13%) are fair, 14 items (54%) are good, and 9 items (30%) are very good. In terms of distractor effectiveness, 5 items (13%) are less effective and need revision, while 25 items (87%) are effective and suitable for use. It can be concluded that the Arabic test items for Grade VIII at MTsN 6 Lima Puluh Kota are of fairly good quality and can be reused.